Changes in brain functional connectivity associated with transcutaneous auricular vagus nerve stimulation in healthy controls - Monti, Daniel A.; Wintering, Nancy; Vedaei, Faezeh; Steinmetz, Alicia; Mohamed, Feroze B.; Newberg, Andrew B. (Frontiers in Human Neuroscience, 2025)
PurposeA growing number of research studies have explored the potential effects of vagus nerve stimulation (VNS) on brain physiology as well as clinical effects particularly related to stress and anxiety. However, there currently are limited studies showing functional changes during different frequencies of stimulation and laterality effects transcutaneous auricular VNS (TaVNS). In this study, we evaluated whether TaVNS alters functional connectivity in the brain of healthy controls. We hypothesized that TaVNS would significantly alter connectivity in areas involved with emotional processing and regulation including the limbic areas, insula, frontal lobe regions, and cerebellum.MethodsWe enrolled 50 healthy controls. Participants were placed in the MRI scanner with MRI compatible ear buds that provided TaVNS. Subjects underwent TaVNS in the left, right, and both ears in a randomized manner during the MRI session. Stimulation was provided for 5 min on and then there was a 5 min off period in between. To evaluate the primary outcome of neurophysiological effects, all participants received blood oxygen level dependent (BOLD) functional magnetic resonance imaging (fMRI) during the TaVNS on and off states.ResultsThe results demonstrated significant changes in functional connectivity during TaVNS that differed depending on the frequency of stimulation and which ear was stimulated. In general, areas of the brain that had altered functional connectivity included the frontoparietal regions, limbic regions, insula, and cerebellum. Interestingly, cognitive areas were also involved including parts of the temporal lobe, salience network, and default mode network.ConclusionThis study is an initial step toward understanding the functional connectivity changes associated with TaVNS. The findings indicate significant brain changes, particularly in areas that are involved with emotional processing and regulation, as well as cognition. Future studies can expand on this data and focus on specific patient populations to determine the effects of TaVNS.